A Thematic Study of Selected Aḥadīth on Chastity - Lababidi, Abdullah (Journal of Islamic and Religious Studies, 2020)
One of the most dangerous temptations that a person faces in his life, is the temptation of the Devil to him. In order not to be a tool for Satan's tricks, it is necessary for him (person) to comply with Allah and His Messenger in terms of commands and prohibitions. Chastity is considered one of the morals that help the Muslim to succeed in his battle with Satan, So this research sheds light on this great moral and explains its importance in preserving the cohesion of family and society by collecting the Aḥādith mentioned in the Prophet’s Sunnah related to this term. The researcher used the deductive approach in analyzing the Ahadith. The research results that Chastity is not limited to abstaining from desires that God Almighty has forbidden rather, it is an abstinence from everything that is despised and estranged by law and custom, and among its results is the realization of faith in Allah Almighty.